THE CONSEQUENCES OF THE «COTTON AFFAIRS» POLICY (A CASE STUDY OF SURKHANDARYA REGION) - Nazarov Otabek Muzrobovich (Western European Studies, 2025)
The article analyzes information about the «cotton affair» and «Uzbek affair,» a socio-political campaign that took place in the Uzbek SSR, including the Surkhandarya region, in the 1980s. This company, which was part of the «perestroika» process in the Soviet Union, was analyzed using archival documents, researched scientific works, and literature.
Keywords: raw cotton; social crisis; corruption; personnel policy